Artificial Intelligence in the Classroom: Opportunities and Challenges for Teachers and Students - Rosero Ordóñez, Sandra Lorena (2025)
This study analyzes the integration of artificial intelligence (AI) and robotics in education, assessing their impact on 200 teachers and students. A mixed-methods approach was employed, combining surveys, interviews, and field observations to collect data on participants’ perceptions and experiences. The findings indicate that 75% of respondents believe these technologies foster personalized learning; however, 58% reported technological difficulties, and 62% emphasized the need for teacher training. The discussion highlights that, although 75% of teachers employ basic digital tools, the effective integration of AI and robotics requires overcoming challenges related to infrastructure and teacher professional development.